On the nucleons motion in the nucleus as being due to realistic inter-nucleonic forces - Lyakhno, Yu.P. (Вопросы атомной науки и техники, 2017)
This paper deals with the possible motion of nucleons in the nucleus, which is due to realistic inter-nucleonic forces. This approach provides new or more substantiated conclusions about the nuclear structure than those based on the effective interaction of nucleons, while the shell model of the nucleus may lead to questionable conclusions regarding the nuclear structure and nuclear reaction mechanisms. Обговорюється можливий рух нуклонів в ядрі, обумовлений реальними міжнуклонними силами. Це дозволяє здобути нові або більш обґрунтовані висновки про структуру ядра, ніж на основі ефективної взаємодії нуклонів. Оболонкова модель ядра може привести до сумнівних висновків про структуру ядра і механізми ядерних реакцій. Обсуждается возможное движение нуклонов в ядре, обусловленное реальными межнуклонными силами. Это позволяет получить новые или более обоснованные выводы о структуре ядра, чем на основе эффективного взаимодействия нуклонов. Оболочечная модель ядра может привести к сомнительным выводам о структуре ядра и механизмах ядерных реакций.